The 2021 battery technology roadmap. (16th February 2021) - Ma, Jianmin; Li, Yutao; Grundish, Nicholas S; Goodenough, John B; Chen, Yuhui; Guo, Limin; Peng, Zhangquan; Qi, Xiaoqun; Yang, Fengyi; Qie, Long; Wang, Chang-An; Huang, Bing; et al.
Abstract: Sun, wind and tides have huge potential in providing us electricity in an environmental-friendly way. However, its intermittency and non-dispatchability are major reasons preventing full-scale adoption of renewable energy generation. Energy storage will enable this adoption by enabling a constant and high-quality electricity supply from these systems. But which storage technology should be considered is one of important issues. Nowadays, great effort has been focused on various kinds of batteries to store energy, lithium-related batteries, sodium-related batteries, zinc-related batteries, aluminum-related batteries and so on. Some cathodes can be used for these batteries, such as sulfur, oxygen, layered compounds. In addition, the construction of these batteries can be changed into flexible, flow or solid-state types. There are many challenges in electrode materials, electrolytes and construction of these batteries and research related to the battery systems for energy storage is extremely active. With the myriad of technologies and their associated technological challenges, we were motivated to assemble this 2020 battery technology roadmap.